2011
DOI: 10.1007/s10157-011-0508-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of albuminuria in diabetic nephropathy

Abstract: Patients suffering from diabetic nephropathy, resulting in end-stage renal failure, are increasing in number. Pathophysiology of diabetic nephropathy remains to be fully investigated. In clinical settings, the presence of albuminuria/overt proteinuria and low glomerular filtration rate may predict poor renal prognosis, however, the prognosis of normoalbuminuric renal insufficient diabetic patients remains contravertial. In addition to the measurement of urinary albumin excretion, biomarker studies to detect di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 38 publications
(29 reference statements)
1
22
0
1
Order By: Relevance
“…In addition, cardiovascular diseases and deaths increase in patients with diabetic nephropathy before and after dialysis [2][3][4]. Therefore, to determine and manage risk factors for progression of renal and cardiovascular outcomes and mortality is of importance to prolong the life expectancy of diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cardiovascular diseases and deaths increase in patients with diabetic nephropathy before and after dialysis [2][3][4]. Therefore, to determine and manage risk factors for progression of renal and cardiovascular outcomes and mortality is of importance to prolong the life expectancy of diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…The early stage of DN is clinically characterized with persistent micro-albuminuria and multiple renal pathological injuries 3 . Early morphological alterations in DN include glomerular hypertrophy, mesangial matrix expansion and GBM thickening 4, 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The stages in pathogenesis involve diabetic microalbuminuria, macroalbuminuria, and renal failure. Multiple factors are involved including blood glucose, blood lipid, and insulin resistance (4,5). Additionally, inflammatory reactions were also recognized to play an essential role in each stage of the diabetic nephropathy (6).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a few studies reported H. pylori infection in different stages of diabetic nephropathy (19). We hypothesize that H. pylori infection in the pathogenesis of systemic inflammation and vascular endothelial damages suggests a significant association Page 5 of 27 A c c e p t e d M a n u s c r i p t 4 between H. pylori infection and urinary protein, which is a hallmark of progression of diabetic nephropathy. We therefore investigated the prevalence of H. pylori infection in patients with type 2 diabetes mellitus and diabetic nephropathy and investigated if different stages of diabetic nephropathy showed higher level of urine protein and inflammatory mediators in infected than in non-infected patients.…”
Section: Introductionmentioning
confidence: 99%